Construction of a portable immunosensor for the sensitive detection of carbendazim in agricultural products using a personal glucose meter. (1st May 2023) - Liu, Haoran; Xie, Longyingzi; Wang, Yiwen; Liu, Yanlin; Fu, Ruijie; Cui, Yongliang; Zhao, Qiyang; Wang, Chengqiu; Jiao, Bining; He, Yue
Highlights: A portable immunosensor for the detection of carbendazim was established. A personal glucose meter was designed as signal reading device. A low detection limit of 0.37 ng/mL for carbendazim was achieved. Good performance for citrus and cabbage analysis was demonstrated. Abstract: Portable and sensitive detection of carbendazim (CBD) is highly desirable for food safety and environmental protection. Herein, a portable immunosensor for the sensitive detection of CBD is proposed based on alkaline phosphatase (ALP)-labeled and secondary antibody-modified gold nanoparticles (AuNPs). The quantification is based on ALP catalyzing the dephosphorylation of glucose-1-phosphate disodium salt to generate glucose, thus converting the concentration of CBD into glucose, thereby realizing the portable detection of CBD by personal glucose meter. Benefiting from signal amplification strategy that integrates the large specific surface area of AuNPs, the enzymatic reactions of terminal deoxynucleotidyl transferase and ALP, a low detection limit of 0.37 ng/mL for CBD is achieved. When this portable method is used to analyze citrus fruit, canned citrus, and cabbage, good-consistency results are obtained with the UPLC-MS/MS method. The good performance demonstrates the great potential of this portable method for CBD monitoring in resource-poor settings.